Performance Comparison of H2O and CO2 as the Working Fluid in Coupled Wellbore/Reservoir Systems for Geothermal Heat Extraction - Lei, Hongwu (Frontiers in Earth Science, 2022)
Owing to its high compressibility and expansivity as well as low viscosity, which can possibly replace water, CO2 is considered as a novel heat-transmission fluid for extracting geothermal energy from enhanced geothermal systems (EGS). For the performance comparison of CO2 and H2O as the working fluid, a classical five-spot model based on the geologic and geothermal conditions at the Songliao Basin, China, is constructed. Results obtained from the coupled wellbore/reservoir model reveal that the (1) net heat extraction and flow rate are greater for CO2 than for water at a fixed operation pressure difference between the injection and production wellheads, but the wellhead temperature is far lower for CO2 than for water due to the strong Joule–Thomson effect of CO2 in the wellbore. (2) A stronger pressure change in the wellbore is observed by using CO2, attributed to the gravity and high flow velocity of CO2; this pressure change induces a relative drop in the frictional pressure. For CO2, the enthalpy change in the wellbore is mainly contributed by the gravitational potential, while for H2O, the enthalpy changes in the wellbore is contributed by the gravitational potential and lateral heat exchange. (3) The heat extraction performance depends on the operation pressure difference and injection temperature for water-based EGS, while it depends on the pressures of injection and production wellheads as well as the injection temperature for CO2-based EGS. A high operation pressure is favorable for improving the heat extraction performance (especially the production temperature) for CO2. (4) With the temperature drop limitation at the downhole of the production well, the heat extraction performance is better by using water than that by using CO2 as the working fluid. However, the low-power consumption for maintaining fluid circulation, the low reactivity between CO2 and formations, and geologic storage of CO2 also demonstrate the application potential of CO2-based EGS.